ANALISA RESPON GETARAN PADA TURBIN FRANCIS DENGAN MENGGUNAKAN SINYAL SUARA - Helmizar; M.Hapis Apmarwansahrowi; Dedi Suryadi (UNIB Press, 2022)
Damage is very common in the PLTA Hydroelectric francis turbine, usually appearing on parts, clutches, gears, bearings, or other drive components. Proper fault diagnosis can help to reduce or even prevent breakdowns. To identify damage to the turbine can use sound signal analysis. This method analyzes using sound signals. By analogizing vibrations as sound waves produced by mechanical vibrations, it is hoped that the sound signal can be used as a parameter to determine the condition of the turbine. In this study, to get the best signal, a microphone is used as a sensor to capture sound signals which are placed on the guide bearing of the hydropower test turbine. The sound signal in the time domain is then transferred to a signal in the frequency domain using Fast Fourier Transform (FFT). The results of the test showed that there were 2 active frequencies, 1x rpm and 2x rpm at a turbine rotation of 500 rpm for 6 days of testing. These characteristics indicate the identification of the problem of the bent shaft on the turbine.